The determinants of user satisfaction of engineering maintenance system (EMESYS) in the Malaysian army / Nurul Shahnaz Mahdzan ...[et al.] - Mahdzan, Nurul Shahnaz; Mokhtar, Marzuki; M. Nayan, Amran; Idris, Mohd Razif (Universiti Teknologi MARA, 2021)
Engineering Maintenance System (EMESYS) is the online Management Information System (MIS) on equipment maintenance performed by the Royal Electrical and Mechanical Engineers (REME) Corps including maintenance on vehicle, weapon, electronic and miscellaneous equipment. This study attempts to identify the determinants of user satisfaction in adopting the EMESYS based on an information system success model by De Lone and Mc Lean (2003). This study is important as it is the first empirical study focusing on the user satisfaction of EMESYS in the context of the Malaysian Army. The data were collected using online surveys from 309 EMESYS users. Standard multiple regressions was used to analyse the data gathered. The results of this study indicate that three of the hypothesis are supported and users' satisfaction of EMESYS is influenced by the three dimensions, namely, system quality, information quality and IT infrastructure. EMESYS has been proven successful in transforming the tedious procedures involving multiple parties and documents to the process of a simple data entry to EMESYS.